SETTING UP AND CHALLENGES OF RUNNING A GERIATRIC CENTRE: THE EXPERIENCE OF A COMMUNITY-LED GERIATRIC CENTRE SOUTH-WEST, NIGERIA - Moses L. Akinwale (Nigerian Frontline Medicine Journal)
The global population over 60 years is growing rapidly, with the proportion of the over-60 years population expected to double between 2015 and 2050. Life expectancy in Nigeria has risen, leading to increasing demand for the care of the elderly population. The first Geriatric Centre in Nigeria was established at the University College Hospital, Ibadan, in 2012. The interest in geriatric medicine is growing due to demographic shifts, increasing life expectancy, complex health issues, quality of life, economic and social implications, and preventive care. Geriatric centres offer specialised care for older adults, focusing on their medical, psychological, and social needs. Effective geriatric care can reduce healthcare costs by preventing chronic conditions from worsening. Geriatric centres also provide caregiver support, respite care, education, and counselling services. The Ijesaland Geriatric Centre, Ilesa, was established in 2022 by the Ijesaland Community Development Assembly (ICDA) to address the community's health needs and promote harmony, peace, and progress. The project involved constructing and equipping the "Ijesaland Geriatric Centre, Ilesa," to provide promotional, preventive, curative, rehabilitative, and recreational services. The project was completed within nine months, with community and diasporan members actively participating. The Ijesaland Geriatric Centre was built at a cost of one billion naira and completed entirely through community effort before it was transferred to Obafemi Awolowo University Teaching Hospital, Ile-Ife. The centre now sees 1000-1200 patients per month, attracting patients from the six local government areas and adjoining states. The representatives of the community monitor and evaluate the operations, while the management team of the collaborating government institution facilitates employment and staff recruitment. However, there were occasional minor challenges between the Ijesa community and the management of the collaborating institution, leading to occasional service delays and equipment procurement bottlenecks, which were settled at joint meetings, understanding the history, significance, and benefits of geriatric care can help communities better prepare for the challenges and opportunities of an increasingly elderly demographic.